Oribatid mites (Acari, Oribatida) of pine and cypress litter in selected habitats of Sicily (Italy) - Seniczak, Stanisław; Seniczak, Anna (Biological Letters, 2014)
Oribatid mites live in the soil or plant matter and usually feed on living and dead plant or fungal material, lichens, carrion, or some species are rarely predatory. Oribatid communities were investigated in litter under pine and cypress trees in selected locations in Sicily: Etna slopes (near Rifugio Sapienza and near Castiglione di Sicily), coastal town Giardini Naxos, Archaeological Museum in Agrigento, and Archaeological Park in Sagesta. The most abundant and diverse oribatid mites lived in cypress litter in Agrigento and on Etna slope. The lowest numbers of individuals and species were recorded in pine litter in Agrigento. In the oribatid mite communities, only 1-3 species were abundant, so the values of Shannon H’ index, and Pielou EPielou and Hurlbert EHurlbert evenness indices were rather low. Their values were the highest in pine litter near Rifugio Sapienza, located nearest to the crater of Etna, while the lowest in pine litter in Agrigento. The former habitat was rich in oribatid mites and species, with a large participation of small species, like Suctobelbella subcornigera, Brachychthonius impressus, and Liochthonius simplex, which made up nearly 63% of the total number of oribatid mites within that habitat. In other habitats, usually Oribatula propinqua dominated, but in pine and cypress litter in Giardini Naxos, Oppiella nova and Ramusella clavipectinata were the most abundant, respectively. Among oribatid mites, adults usually dominated, but Adrodamaeus femoratus, Aphelacarus acarinus, Brachychthonius impressus, Liochthonius simplex, Cosmochthonius reticulatus, Metabelba pulverulenta and Pilogalumna crassiclava were rich in juveniles.